CONTENT OF THE PLANT CISTANCHE MONGOLICA GROWN IN KHOREZM SOIL CLIMATIC CONDITIONS (CAHIERS MAGELLANES-NS, 2024)
A detailed examination of the chemical composition of Cistanche mongolica, a plant species indigenous to the Khorezm oasis, has been conducted for the first time. This investigation was undertaken to assess the plant's adaptability to the region's extreme climatic conditions by analyzing the distribution of macro- and microelements, flavonoids, vitamins, and amino acids across its root, shoot, and flower systems. A comparative analysis with Cistanche mongolica specimens from other regions of the republic and China identified both significant similarities and distinct differences in their chemical profiles. Comparative phytochemical analysis of Cistanche specimens collected from northwestern regions of our country and China revealed substantial compositional similarities, as well as distinct differences in their chemical profiles.The elemental analysis identified potassium, sodium, calcium, and iron as the predominant elements in the plant, with concentrations measuring 245.7 × 104 µg/g, 45.15 × 104 µg/g, 14.65 × 104 µg/g, and 1.43 × 104 µg/g, respectively. Elemental analysis revealed that potassium, sodium, calcium, and iron were the predominant elements in the plant material, with concentrations of 2.457 × 106 μg/g, 4.515 × 105 μg/g, 1.465 × 105 μg/g, and 1.43 × 104 μg/g, respectively. These elements exhibited significantly higher concentrations compared to other detected elements. The plant's flavonoid profile included apigenin, hypolaetin, rutin, and gallic acid. Additionally, vitamins B2, B6, B9, B12, and PP were detected.Amino acid analysis across the shoot, flower, and root systems revealed a complex composition, with 20 different amino acids identified. Of these, serine, glutamine, cysteine, proline, valine, methionine, leucine, and tryptophan were found in significant quantities, ranging from 1.173151 µg/g to 6.87511 µg/g. These findings indicate that Cistanche mongolica is a nutrient-dense plant species, with a chemical composition that is comparable to, or even superior to, other species. The study’s results enhance our understanding of the plant's nutritional value and its potential applications.